Photoluminescence properties of arsenic and boron doped Si3N4 nanocrystal embedded in SiNxOy matrix. (7th March 2018) - Puglia, Denise; Sombrio, Guilherme; Reis, Roberto dos; Boudinov, Henri
Abstract: Photoluminescence emission of Si3 N4 nanocrystals embedded in SiN x O y matrices was investigated. Nanocrystals were grown by annealing of silicon oxynitride films deposited by sputtering, passivated in forming gas atmosphere and implanted with boron and arsenic. Emission energy was tuned from green to ultraviolet by changing the composition of SiN x O y matrices. Structural characterization of the nanocrystals was performed by Transmission Electron Microscopy. Photoluminescence at room and low temperatures was analyzed and the results suggest that light emission originates in the interface between the nanocrystals and the matrix. The highest photoluminescence intensity at room temperature was achieved by arsenic doped silicon oxynitride films deposited with an excess of nitrogen.